Politeness Strategies Use in the Family Members - Dharma, Ketut Pande Bagus Wahyu Surya; Adnyani, Luh Putu Sri; Ramendra, Dewa Putu (Universitas Pendidikan Ganesha, 2023)
Language is essential in social interaction. It is used by society to communicate with others. Besides, language in society is used as a means of communication to express ideas, intentions, opinions, and purposes. In addition, language also has the function of expressing someone’s feelings and emotions. Politeness becomes one of the crucial things to maintain the conversation running well in society. The communication starts from the small circle and then comes to the big circle. The small circle for example in family members is one of the communications that can begin before going to society. Therefore, the present study aimed to analyze the types of politeness strategies used by Rimbi’s family members. This research was categorized as descriptive qualitative research. A descriptive qualitative research design was used to describe the positive politeness in family member conversations. There were 5 members chosen as the subjects in this research. It consisted of a father, a mother, and 3 sisters. The research data were the script of conversation in the form of sentences, clauses, or words. The findings show that the family members rarely use negative politeness despite that bald-off record and off record become the most used strategies use in the family members.